Opportunities for Waste to Energy in the Milk Production Industry: Perspectives for the Circular Economy - Miguel Casallas-Ojeda (MDPI AG, 2021)
Cheese whey is a waste produced in the dairy industry which generates problems if it is dumped directly into the sewer due to its high organic load. An alternative for cheese whey management is anaerobic digestion, a biological process that transforms organic matter into biogas and digestate, two products with significant energy and agricultural potential. This work was aimed at contributing to the building of knowledge about the anaerobic degradation of cheese whey, developing a bibliometric analysis, and tracing trends in related research from 2010 up to the present, using PRISMA® to develop a systematic review based on Scopus® and using Excel® and bibliometric software (VosViewer® and RefViz®) for the identification of information. Our results show that the research around cheese whey is relatively recent and that the highest percentage of publications is from 2018 onwards. Twelve variables of the anaerobic cheese whey degradation process were identified and grouped into five factors: substrate, reactor configuration, digestate analysis, microbiological analysis, and inoculum. Likewise, it was identified that most of the anaerobic processes allow the implementation of the circular economy into the dairy sector. In conclusion, the application of anaerobic digestion in the dairy sector can help to close the productive cycles, produce biofuels, and reduce pollution.